ANALISIS YURIDIS TERHADAP SKEMA KORUPSI KORPORASI DALAM KASUS DUTA PALMA GROUP: IMPLIKASI TERHADAP TATA KELOLA PERUSAHAAN DAN PERTANGGUNG JAWABAN PIDANA - Sandi, Maryam Priska Asmara; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This research aims to analyze in depth the corruption schemes that occur within the PT Duta Palma Group corporation. This analysis will focus on the juridical aspect, by exploring the implications of these acts of corruption on good corporate governance and the forms of criminal liability that can be imposed. Through a qualitative approach, this research will examine various legal sources, company documents, and related literature to identify the types of corruption acts carried out, their implementation mechanisms, and the parties involved. Apart from that, this research will also analyze the extent to which the existing corporate governance at PT Duta Palma Group has failed to prevent criminal acts of corruption. It is hoped that the research results can contribute to developing understanding of corporate corruption in Indonesia, especially in the context of corporate governance. It is also hoped that the findings of this research can provide recommendations for law enforcers, policy makers and companies to prevent similar corrupt practices from occurring in the future.Keywords: Corporate Corruption, PT Duta Palma Group, Corporate Governance, Crime